PENGARUH KOMPETENSI DAN INDEPENDENSI TERHADAP KUALITAS HASIL PEMERIKSAAN DENGAN ETIKA AUDITOR SEBAGAI VARIABEL MODERASI (Studi Empiris Pada BPKP Provinsi Jawa Tengah) - Angelia Irma Yunita, 14.05.62.0019; Jaeni, Jaeni (Students' Journal of Accounting and Banking, 2018)
ABSTACT This study aimed to get empirical evidnce about the impact of competence and independence on the quality of examination resultswith auditor ethics as a moderation variable at a BPKP province of Central Java. Independent variables es used in this study are competence and independence. The dependent variabel used in this research isquality of examination results. The moderation variable in this research is Auditor Ethics. The object of this research is BPKP province of Central Java. The sample in this study are PNS who have followed the education and training as an auditor (Training JFA). The sampling technique used in this study is the purporsive sampling, while data analysis with multiple regession. Results from this study showed thatthe competence have a positive and significant impact on audit quality. Independence have a positive and significant impact on quality of examination results. Auditor Ethicshave a positive and significant impact on quality of examination results. Auditor ethics moderates the relationship between competency and the quality of examination results by the BPKP province of Central Java.Auditor ethics moderates the relationship between independence and the quality of examination resultsby the BPKP province of Central Java. Keywords: Quality Of Examination Results, Competence, Independence, Auditor Ethics